Orthosiphon Stamineus as Anti-Inflammatory and Diuretic in Gout Arthritis Disease - Dedi Daryanto (Jurnal Penelitian Perawat Profesional, 2020)
Orthosipon Stamineus or cat's whiskers is one of the herbs that has various pharmacological effects including anti-inflammatory diseases and gout arthritis as a diuretic, so that Orthosipon Stamineus is often used as an herbal remedy. The purpose of this literature review is to know the effect of cat's whiskers plants as anti-inflammatory and diuretic in gout arthritis patients. The sources used are from 21 articles PubMed NCBI, Google Schoolar, and Elsevier, and only 16 articles were used from 1994 to 2019 years. Result of 16 journals called later in the analysis using the Systematic Literature Review method is by collecting, evaluating, and developing research on a particular focus topic. From some research done obtained the result that cat's whiskers plants are beneficial as anti-inflammatory by lowering the formation of TNFa and IL1. The active compounds of flavonoids and phenolic that are found in Orthosipon Stamineus can suppress inflammatory reactions and contain diuretic compounds that lower purine levels in the body.